2019
DOI: 10.1007/s13671-019-0252-2
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Teledermatology: Theory and Practice

Abstract: Purpose of Review Multiple factors influence the success and failure of teledermatology programs. We evaluate the current teledermatology literature using the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) framework developed for implementation research. We introduce this framework to encourage a thorough examination of teledermatology's implementation including its sustainability. In this way, programs can better realize teledermatology's promise for enhancing patients' access to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 90 publications
(101 reference statements)
0
21
0
Order By: Relevance
“…To prioritize implementation outcome collection of the new TD process across the RE-AIM framework, we distributed a survey of previously published potential RE-AIM outcomes to TD leadership (see Table 1 for a list of implementation outcomes; four medical directors of pilot sites and three Duke Dermatology leaders). 13,20 We created a TD dashboard to collect real-time implementation outcomes important to the leadership, prioritizing outcomes rated highly by primary care and dermatology leadership (Table 1). The dashboard aggregated TD implementation and patient outcomes from the EHR.…”
Section: Measuring Implementation Outcomesmentioning
confidence: 99%
“…To prioritize implementation outcome collection of the new TD process across the RE-AIM framework, we distributed a survey of previously published potential RE-AIM outcomes to TD leadership (see Table 1 for a list of implementation outcomes; four medical directors of pilot sites and three Duke Dermatology leaders). 13,20 We created a TD dashboard to collect real-time implementation outcomes important to the leadership, prioritizing outcomes rated highly by primary care and dermatology leadership (Table 1). The dashboard aggregated TD implementation and patient outcomes from the EHR.…”
Section: Measuring Implementation Outcomesmentioning
confidence: 99%
“…Teledermatology in our country will be built on the momentum due to the pandemic and carry into the future. Few studies have evaluated strategies used to integrate or sustain teledermatology into existing healthcare systems 10,11 . This type of research, called implementation science, provides information about the entire process of teledermatology, such as planning, adopting, maintaining, and the effect of intervention 10,12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have evaluated strategies used to integrate or sustain teledermatology into existing healthcare systems. 10,11 This type of research, called implementation science, provides information about the entire process of teledermatology, such as planning, adopting, maintaining, and the effect of intervention. 10,12,13 Thus, the barriers and facilitators of teledermatology can be identified and a more successful integration process can be achieved.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that TD services achieve diagnostic accuracy and clinical outcomes comparable to in-person dermatologic consultations. 9 , 10 Furthermore, recent evaluations of TD programs targeted at low income populations showed that TD improved access to dermatologic care without increasing the volume of total dermatologic visits. 11 , 12 , 13 This suggests that increased adoption of TD has the potential to increase the efficiency of case triage.…”
Section: Introductionmentioning
confidence: 99%